Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Review - Page 904: 9


$(f \circ g)(-1) = -2$

Work Step by Step

Functions involved: $f(x)=x^2-2$ $g(x) = x+1$ Substitute $g(x)$ into $f(x)$: $(f \circ g)(x) = (x+1)^2-2$ Substitute $-1$ into $(f \circ g)(x)$: $(f \circ g)(-1) = (-1+1)^2-2$ $(f \circ g)(-1) = (0)^2-2$ $(f \circ g)(-1) = -2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.